Sentidos atribuídos às políticas públicas de inclusão dos catadores pelos atores envolvidos nas discussões dos resíduos sólidos - Feitosa, Larissa de Brito (2011)
The activity of the "catadores" of recyclabe materials arises in the context of the capitalist system that deepens social differences, exacerbates poverty and undermines the rights, to expel workers in the formal market, given the requirements arising from investment in technology that intensifies the competition, making the activity an alternative precarious survival. In the case of the city of Fortaleza, with the deactivation of the former landfill located in the neighborhood Jangurussu, these workers migrate and multiply throughout the city, showing the poverty and other social issues were previously restricted to the periphery of the city, reflecting mainly a social condition , economic, political and environmental dimensions of a territory. The recent enactment of a law that effectively the National Policy on Solid Waste awakens to the importance of intensifying dialogue on waste management issues in large cities, the role of the interventionist state, especially the inclusion of those workers and public awareness on environmental issues and social urgency. In general, aims to analyze the meaning assigned by recyclable material "catadores" and representatives of both government and civil society initiatives in the face of the organization and management groups of scavengers, promoted by entities linked to public policies. For the research, were used mainly focus groups and participant observation as a collection technique, and a field diary and interviews for further analysis based on the content. It is noticed that despite the discussions generated around the law, are necessary and concrete actions planned with the participation of all actors involved and engaged in the issue of solid waste in Fortaleza, mobilized, especially by public authorities. Unfortunately, the actions remain so going off, isolated and discontinuous, weakening and wasting resources which if well managed, could promote important changes, especially to the strength and cohesion of groups and activity